Low bone mass and hypovitaminosis D in haemophilia: A single‐centre study in patients with severe and moderate haemophilia A and B. Issue 5 (25th August 2020) - Linari, Silvia; Melchiorre, Daniela; Pieri, Lisa; Tofani, Lorenzo; Fanelli, Alessandra; Brogi, Marco; Castaman, Giancarlo
Abstract: Introduction: Haemophilia (H) is frequently associated with a multifactorial reduction in bone mineral density (BDM), but little is known about possible differences between HA and HB according to their severity. Aim: To evaluate the association between low bone mineral density (BMD), 25‐hydroxyvitamin D [25(OH)D] concentrations and bone turnover markers in patients with HA and HB younger or older than 50 years. Methods: In 78 patients <50 years and 33 patients >50 years with severe (S) or moderate (M) HA and HB, BMD was measured by dual‐energy X‐ray absorptiometry at femoral neck (FN) and lumbar spine and then correlated to annual bleeding rate (ABR), World Federation of Haemophilia orthopaedic joint scale (WFH score), 25(OH)D concentrations, parathyroid hormone (PTH), amino‐terminal telopeptide of type 1 collagen (NTx), urinary pyridinolines, osteocalcin and bone‐specific alkaline phosphatase. Results: Overall, a high prevalence of hypovitaminosis D was diagnosed. In patients <50 years, low FN‐BMD was significantly more frequent in HA than in HB, while PTH, pyridinolines, ABR and WFH score were associated with H type and severity. In patients >50 years, similarly low FN‐BMD was observed in HA and HB, while ABR and WFH score were associated with H type and severity, being milder in HB. Conclusions: Low bone mass is a frequent comorbidity in haemophilic patients of all ages, apart from those with MHB. Clinical and laboratory assessments confirm a higher bone impairment and faster bone resorption in HA compared with HB. Looking at H type and severity, MHB seems to have a normal bone metabolism and a less severe disease.